Systematic study of rare-earth ions size-dependent structural phase transition from monazite to zircon-type in rare earth chromates using Raman spectroscopy - Ughade, Supriya; Poddar, Pankaj (Journal of Raman Spectroscopy, 2023)
Rare earth chromates (RCrO4) undergo monazite to zircon-type structural phase transition due to a decreased rare-earth ion size. They also exhibit an intermediate mixed phase. However, there is no systematic study on the influence of structural distortion on their phononic behavior, which is quite sensitive to subtle environmental variations. A change in the room temperature phononic spectrum was studied in the family of RCrO4 compounds, where R was varied from La to Yb using Raman modes. With an increase in the atomic number from Nd to Yb for zircon-type phases, the external translational and rotational modes were observed to shift towards lower and higher wavenumbers, respectively. At the same time, all internal vibrational modes shifted towards higher phonon energies. A comparison between Raman modes for monazite, intermediate, and zircon-type RCrO4 phases showed a gradual shift in the internal modes towards a higher wavenumber. The confirmation of the change in Raman modes with the decreasing radius was found by comparing the rare-earth elements in DyCrO4 and LaCrO4 with non-rare-earth elements in YCrO4.
Keywords: monazite-type; Raman spectroscopy; rare earth chromates (RCrO4); YCrO4; zircon type